Feasibility of Ice Segregation Location by Acoustic Emission Detection: A Laboratory Test in Gneiss - Duca S.; Occhiena C.; Mattone M.; SAMBUELLI, Luigi; SCAVIA, Claudio (Permafrost and Periglacial Processes, 2014)
Large slope failures in steep alpine bedrock present significant geological hazards. Ice segregation is thought to be one of the mechanisms involved in high-mountain bedrock fracture but has not been reproduced experimentally in hard, intact rock. Here, we report results from a 3 month freezing experiment that aimed to reproduce ice-lens growth at the interface between the active layer and permafrost in a 15 cm cube of hard, intact rock (Arolla gneiss). Monitoring of acoustic emissions (AEs) recorded the propagation of microcracks horizontally through the block, resulting in a continuous and thick macrocrack near the base of the artificial active layer. Microcracking occurred within an approximate temperature range of 0.5 °C to 2.7 °C, consistent with ice segregation theory. Hypocentres of recorded AE events were concentrated in a 40mm thick band between depths of 4.5 and 8 cm in the block. The band approximately coincides with the frozen fringe and indicates that ice segregation can induce micro- and macrocracking in gneiss.